The Role of Online Discursive Action in Subjects' Emancipatory Repositioning in Egypt: Assault Police Case Study - Guirguis, Christine Saad, MA (AUC Knowledge Fountain, 2023)
The current study's central question is how social change is discursively constructed. I studied an online feminist social movement that sparked in Egypt on Instagram in July 2020 and labeled "Assault Police." Within the critical social theory and feminism framework, I reviewed the literature on (critical) discourse, social change, and social movements. I tried to unravel the complexity around emancipation as a vital concept in the current study. I located and discussed areas of tension and identified a conceptualization that loosens the theoretical entanglement around it. The research problem sought to specify how the online discursive action facilitated desired outcomes of dominance resistance. For this purpose, I conducted Critical Discourse Analysis (CDA) using multimodal analysis techniques to investigate Assault Police's published posts on Instagram—where it started. Additionally, I analyzed two newspaper and one T.V. interviews with the social movement's founder to get a well-rounded idea of the social movement's backstage and how it supported its outbreak. The findings showed that the social movement's struggle relatively succeeded in re-positioning subjects through discourse. Moreover, it interpreted the struggle as a resistance against power abuse backed by power imbalance and oppressive ideologies.